2006
DOI: 10.1097/01.bcr.0000194276.36691.fb
|View full text |Cite
|
Sign up to set email alerts
|

Semapimod Reduces the Depth of Injury Resulting in Enhanced Re-epithelialization of Partial-Thickness Burns in Swine

Abstract: Studies suggest that tumor necrosis factor alpha (TNF-alpha) plays a role in burn pathogenesis. We conducted a randomized controlled experiment in swine to determine whether a novel macrophage inhibitor, semapimod (formerly known as CNI-1493), would blunt the local production of TNF-alpha, interleukin (IL)-1, and IL-6 in burns leading to less injury extension and faster re-epithelialization. After creating second-degree burns, animals received one or two intravenous boluses of semapimod 1 mg/kg or normal salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…4,5,[22][23][24]123,49 Perhaps, future research regarding the progression of burn wounds will be centered on the development of small molecules capable of blocking steps in these pathways, which are common to multiple mediators. Indeed, the promise of such intervention is highlighted by the work of Giles et al, 25 who have already successfully used topical administration of c-Jun in burned mice.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[22][23][24]123,49 Perhaps, future research regarding the progression of burn wounds will be centered on the development of small molecules capable of blocking steps in these pathways, which are common to multiple mediators. Indeed, the promise of such intervention is highlighted by the work of Giles et al, 25 who have already successfully used topical administration of c-Jun in burned mice.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, modulating acute inflammation using p38MAPK inhibitor was shown to be effective in reducing cellular apoptosis, but the long‐term effect of such treatment was unclear. Singer and coworkers have also demonstrated 30% reduction in depth of hair follicle necrosis after systemic delivery of semapimod in a pig model, while systemic delivery of curcumin has shown a positive effect in reducing burn wound progression by 50% in a rat comb burn model 7 days after initial burn . However, systemic delivery of anti‐inflammatory agents in a burn patient increases the risk of secondary complications, and local delivery of TNF‐α neutralizing agent from a HA delivery vehicle has reduced necrosis by up to 70% post‐burn in a rat model.…”
Section: Discussionmentioning
confidence: 98%
“…In a rat model, topical application of inhibitor of p38MAPK, a potent stimulator of pro‐inflammatory cytokine production and promoter of apoptosis, on burn injuries has shown significant reduction of local TNF‐α, IL‐1β, and IL‐6 expression, attenuation of dermal neutrophil sequestration, and a lower level of hair follicle cell apoptosis within 24 hours of the initial burn injury . Intravenous injection of semapimod, a selective inhibitor of macrophage activation, 1 hour after burn in a swine model reduced depth of cellular necrosis and thrombosis, resulting in faster reepithelialization . These studies have successfully demonstrated that early intervention of inflammatory modulation can potentially halt burn wound progression, but developing a targeted method for accomplishing this without significant risks of systemic complications has not been achieved.…”
mentioning
confidence: 99%
“… 35 Several groups reported that topical application of inhibitors of tumor necrosis factor α production or anti- tumor necrosis factor α antibodies reduced the inflammatory response and lessened burn wound progression in pigs. 36 , 37 Taira et al . reported that Rosiglitazone, an insulin sensitizer that enhances the responses of the target cells to insulin, reduces burn progression in rats.…”
Section: Discussionmentioning
confidence: 99%